Covid-19 Distance Teaching-Learning Modes: Which do Mathematics Education Students Appreciate and Prefer? - Luna, Charita A.; Roble, Dennis B.; Rondina, Janneth Q. (SCAD Independent, 2022)
The study determined which distance teaching-learning mode of instruction during COVID-19 pandemic period is best appreciated and preferred by mathematics education students. It utilized a qualitative method of research which does not use standard instruments. It used the actual mode of instruction the respondents received from their teachers which they have listed and from among the list, they chose one as the best. It utilized BSED mathematics major students for school year 2020-2021 and 2021-2022, taking mathematics subjects of the University of Science and Technology of the Philippines, Cagayan de Oro City campus. Frequency, percentages and qualitative analysis of the data from respondents’ feedback on the mode of online instruction they experienced and the results revealed that the distance teaching-learning mode using Work text with whiteboard in Google meet for discussion and recording of classroom discourse was chosen the best mode of instruction. The researchers recommend that teachers in distance teaching-learning process may use the mode which uses Work text, whiteboard for discussion with recording of the whole classroom discourse episodes.